Peran Lynk.Id dalam Membangun Personal Branding dan Produk - Ahmad Ikhsan Affandi; Arya Nando Prakoso; Rifki Eko Satrio; Andreka Dwiki Cahya; Fauzi Fauzi (CV. ITTC INDONESIA, 2025)
The advancement of digital technology has transformed the way individuals build their personal branding and distribute digital products efficiently and widely. One notable innovation in this area is Lynk.id, a platform that offers an integrated solution for content creators, micro-entrepreneurs, and professionals to showcase their portfolios, services, and digital products through a single, customizable link. This study aims to analyze the role of Lynk.id in enhancing personal branding and supporting the monetization of digital products among its users. A mixed-methods approach was employed, combining quantitative data from surveys distributed to 100 active Lynk.id users and qualitative insights from user experience studies. The findings reveal that key features of Lynk.id—such as link personalization, social media integration, and streamlined access to payment systems and content distribution—significantly contribute to increased personal visibility and user income. These results indicate that Lynk.id plays a strategic role in shaping a strong digital identity while facilitating the growth of individual-based digital economies.